Challenges and Experiences of Students in the Virtual Classroom World: A Literature Review - Bhavika Pandita Hakhroo (International Journal of Engineering and Management Research, 2021)
The study aims to discuss the experience students face in the virtual classroom mode. The limitations and challenges which students face while enrolling in online modes to learning from MOOC Courses to Distance Learning. The community of the people undertaking online education has increased significantly in the past few years. The paper reviews the literature on the topic of online classes, asynchronous and synchronous modes of delivery, the perception of students in the virtual learning and the experiences and challenges faced.